Thrombocytopenia during the course of acute poststreptococcal glomerulonephritis - Tasic, Velibor; Polenakovic, Momir (The Turkish Journal of Pediatrics, 2003)
A four-year old boy was admitted to the hospital due to acute thrombocytopenic purpura. Three days later he developed edema, hematuria and hypertension. The diagnosis of acute poststreptococcal glomerulonephritis was based upon the evidence of previous sore throat, hypocomplementemia and increased antistreptolysin O titer. Renal biopsy was contraindicated due to throbocytopenia. An extensive work-up was done to exclude mebranoproliferative glomerulonephritis and systemic diseases such as hemolytic uremic syndrome or systemic lupus erythematosus. The clinical outcome of the nephritis and thrombocytopenia was excellent in respect to both conditions. To the best of our knowledge concurrent occurrence of acute thrombocytopenic purpura and poststreptococcal glomerulonephritis is very rare; there are only four similar cases reported in the literature. A careful work-up and follow-up are mandatory to exclude systemic disease.